Generic Hybridity in Three of Lea Aini’s Novels - Ezer, Nancy (MiKAN, 2016)
Using M. M. Bakhtin’s theory on dialogism and hybridity, this paper attempts to foreground the considerations behind generic hybridity in three of Lea Aini’s novels: Someone Must be Here (1995), Ashtoret (1999), and The Rose of Lebanon (2009). The study argues that each of these three novels merges two opposite genres in order to dialogize between a genre and its ‘other’. In the novel Someone Must be Here, Aini manipulates the conventions of the romantic novel, while simultaneously parodizing and subverting them in order to offer new content for the female Bildungsroman. In Ashtoret, she contrasts a normative encyclopedic satire with its de-generative double in order to advocate for the co-existence of oppositional ideologies, which she calls post-Zionist Zionism. In The Rose of Lebanon, she creates a new genre, ‘bio-fiction’, combining her autobiography with a fictional story in order to re-configure herself and her social ‘other’ by both dismantling and constructing their identities. Additionally, the paper exposes the implicit dialogue taking place in Aini’s narratives, in which she negotiates her literary position from the cultural margins where the patriarchal literary hegemony designated women’s writing, trying to inscribe herself into Israeli social and literary history.